Macroeconomic variables and the cross-section of Johannesburg Stock Exchange returns - Paul Van Rensburg (South African Journal of Business Management, 2000)
This study adopts the Chen, Roll Ross prespecified variable approach to priced arbitrage pricing theory factor (APT) identification on the Johannesburg Stock Exchange (JSE). It is observed that the dichotomy in the return generating processes underlying South African mining and industrial shares leads to cross-sectional correlations in the residual errors of linear factor models that do not employ factor analytically extracted explanatory variables. As a result, a 'two residual market factor' approach is introduced in this study. Employing the iterated non-linear seemingly unrelated regression technique of McElroy Burmeister (1988), it is found that the rand gold price, the rate on long bonds, the Dow-Jones Industrial Index and the level of gold and foreign exchange reserves together with the Industrial and All-Gold residual market factors represent priced sources of risk within the framework of the APT over the period 1985 to 1995. The pricing relationships estimated are found to be inconsistent with those implied by the capital asset pricing model. These results are robust across the 'unconstrained intercept' and 'zero beta' cross-sectional model specifications. The findings of the study, however, imply that the influence of macroeconomic variables on the JSE is most parsimoniously expressed in the two factor APT model of Van Rensburg Slaney (1997).